Vulnus amoris: The Transformations of “Love’s Wound” in Medieval Romance Literatures - Gubbini, Gaia (Beihefte zur Zeitschrift für romanische Philologie, 2023)
The concept of love’s wound has haunted European culture for centuries. This book investigates this fundamental concept in Medieval French, Occitan, and Italian literature – with the purpose of tracing its transformation through a selection of medieval literary masterpieces, sacred and profane. The imagery of love’s wound is analysed with multiple approaches, considering also representations of the theme in manuscript illuminations.